LEARNING TAHFIDZUL QUR'AN AT THE EXTRAORDINARY SCHOOL "SAHABAT AL-QUR'AN" IN BINJAI - Rizka Harfiani (Proceeding International Seminar of Islamic Studies, 2021)
The lack of special schools based on Islam and the Qur'an is one of the factors causing children with special needs to not get access to Islamic religious education. Departing from these conditions, the Integrated Islamic Extraordinary School "Sahabat Al-Qur'an" exists as a means for children with special needs to gain access to education by prioritizing Islamic values. This study aims to analyze the learning of Tahfidzul Qur 'an in an integrated Islamic Extraordinary school Sahabat Al-Qur'an located in Binjai City, North Sumatra Province, Indonesia. This research uses a qualitative approach, with the type of field research. Technique data through observation, interviews, and documentation, which then analyzed using interactive analysis, and test the validity of the data using the triangulation method. The implication of the results of this study is to provide an overview of the implementation of Tahfidzul Qur'an learning for children with special needs at school, so that they can carry out their religious obligations as a Muslim who is undergoing normal children.